تطوير منهجية لتحليل وإدارة مخاطر مشاريع السدود في سورية - جراد, فايز; الدبس, هبة (Latakia University Journal -Engineering Sciences Series, 2016)
تعد السدود (Dams) من المشاريع الضخمة والمعقدة , وتتصف بطول ‏فترة التنفيذ عموماً وكلفة التنفيذ الهائلة في بعض الأحيان, فقلّما نُفِّذ سد في سوريا ضمن إمكانيات الخطة التقديرية التي وضعت له من كلفة وزمن ويعود ذلك ‏للمخاطر التي اعترضت تلك المشاريع خلال مرحلة التنفيذ وأثرّت بشكل مباشر على إحدى/ أهداف المشروع الأساسية (كلفة و زمن و جودة).يتناول هذا البحث واقع تنفيذ السدود المتأخر, عن طريق القيام بدراسة للمخاطر التي تعرض لها قطاع التنفيذ وأثرت على أهداف المشروع الأساسية (كلفة – زمن - جودة) , من خلال بحث ميداني يشمل دراسة أكثر من خمس وثلاثين سداً منفذاً في سوريا .وقد استخدمت لهذه الغاية استمارة استبيان تم توزيعها على شريحة من الخبراء والفنيين في السدود , مكنت من الحصول على قائمة بالمخاطر التي يعاني منها تنفيذ السدود بالإضافة لتقييمها , في محاولة لتطوير منهجية علمية لتحليل وإدارة مخاطر مشاريع السدود عن طريق تقييم احتمالات حدوثها وأثرها على أهداف المشروع في حال حدوثها وإدخال معيار جديد للتقييم وهو إمكانية الكشف /السيطرة عليها وذلك وفق منهج FMEA (تحليل نموذج الفشل وآثاره) ودمجه بالمنطق الضبابي, والقيام بترتيب تلك المخاطر ‏وفقاً للدرجة الحرجة (RCN) الخاصة لكل خطر بهدف التنبه المبكر لها مما يمكننا من التعامل معها بالشكل ‏الصحيح ‏مع اقتراح استراتيجيات الرد المناسبة لها.The Dams are large and complex projects, and are generally characterized by the enormous cost of implementation in some cases, and the length of the implementation period, are rarely carried out a dam in Syria within the estimated plan which developed his of the cost and time, this is due to the risks that intercepted projects during the implementation phase and directly influenced the basic project objectives ( cost and time and quality).This research experiences to the reality of the implementation of the late dams, through undertake a study the risks suffered by the implementation of sector and influenced the basic objectives of the project (cost - time - quality), through a field survey study includes more than thirty-five dams in Syria.For this purpose have been used survey was distributed to a slice of experts and technicians in the form of dams, has enabled to obtain a list of the risks faced by the implementation of dams in addition to the assessment, In an attempt to develop a scientific methodology to analyze and manage the risks of dam projects by assessing the probability of their occurrence and their impact on the objectives of the project in the event of occurrence, with introduce a new standard for evaluating a detection / control, As per the approach to FMEA /Failure Mode and Effect Analysis/ and incorporate logic fuzzy, and arrange those risks according the Risk Criticality Number (RCN) for each risk early in order be sensitive to them than we can handled properly with proposing appropriate response strategies.